Simulating real world functioning in schizophrenia using a naturalistic city environment and single-trial, goal-directed navigation - Zawadzki, John A.; Girard, Todd A.; Foussias, George; Rodrigues, Alicia; Siddiqui, Ishraq; Lerch, Jason P.; Grady, Cheryl; Remington, Gary; Wong, Albert H. (Frontiers in Behavioral Neuroscience, 2013)
Objective: To develop a virtual reality platform that would serve as a functionally meaningful measure of cognition in schizophrenia that would complement standard batteries of cognitive tests during clinical trials for cognitive treatments in schizophrenia, be amenable to human neuroimaging research, yet lend itself to neurobiological comparison with rodent analogues. Method: Thirty-three patients with schizophrenia and 33 healthy controls matched for age, sex, video gaming experience and education completed eight rapid, single-trial virtual navigation tasks within a naturalistic virtual city. Four trials tested their ability to find different targets seen during the passive viewing of a closed path that led them around different city blocks. Four subsequent trials tested their ability to return to four different starting points after viewing a path that took them several blocks away from the starting position. Results: Individuals with schizophrenia had difficulties in way-finding, measured as distance travelled to find targets previously encountered within the virtual city. They were also more likely not to notice the target during passive viewing, less likely to find novel shortcuts to targets and more likely to become lost and fail completely in finding the target. Total travel distances across all eight trials strongly correlated (negatively) with neurocognitive measures and, for 49 participants who completed the Quality of Life Scale, psychosocial functioning. Conclusion: Single-trial, goal-directed navigation in a naturalistic virtual environment is a functionally meaningful measure of cognitive functioning in schizophrenia.